Efeito do tucumã (Astrocaryum aculeatum) no metabolismo de nucleotídeos e nucleosídeo de adenina em plaquetas de ratos com hiperlipidemia induzida - Bernardes, Viviane Martins (2018)
Increased levels of lipids in the bloodstream, especially triglycerides and LDL-cholesterol, characterize a lipid disorder called hyperlipidemia, which is one of the major modifiable risk factors for cardiovascular disease. Hyperlipidemia results in aggression to the vascular endothelium in which platelets, seeking to maintain homeostasis, become hyperactive and promote the release of several proatherogenic factors. Among the mediators released by platelets are the nucleotides ATP, ADP, AMP, and the nucleoside adenosine. These molecules act as signals for a complex system involved in the regulation and maintenance of immune responses, denominated purinergic system. This system is also composed by ectoenzymes that have the function of regulating the extracellular levels of nucleotides and nucleosides of adenine. Tucumã (Astrocaryum aculeatum) is a fruit with high therapeutic potential due to its composition rich in carotenoids, flavonoids, fibers, and polyunsaturated fatty acids. Therefore, it may have beneficial actions in the lipid metabolism and in the prevention of cardiovascular diseases. The induction of hyperlipidemia by Poloxamer-407 is a well-established model in the literature, which affects a variety of key enzymes in lipid metabolism, contributing to the investigation of pathological events and therapeutic alternatives in hyperlipidemia. Thus, the objective of the present study was to evaluate the activities of the purinergic system ectoenzymes in platelets of rats with induced hyperlipidemia, treated with tucumã. For the development of this study, 56 adult male Wistar rats were used. The animals were pretreated with vehicle, tucumã extract (250mg / kg), rutin (3.2mg / kg), and β-carotene (6.5mg / kg), administered once daily, via gavage, for 30 days. Rutin and ß-carotene were used as a comparative standard. Hyperlipidemia was acutely induced by an intraperitoneal injection of P-407 (500mg/kg dissolved in sterile 0.9% NaCl solution). The rats were anesthetized with isoflurane and submitted to euthanasia 36h post-induction. Platelets were separated for determination of ectoenzyme activities and serum was used to evaluate biochemical parameters. The induction of hyperlipidemia increased E-NTPDase and E-5'-NT activities and reduced E-ADA activity, possibly as a mechanism for regulating ATP and ADP levels, important agonists of platelet aggregation, and increasing adenosine levels, which has antithrombotic properties. The tucumã extract treatment prevented the increase in ADP hydrolysis, maintaining E-NTPDase activity at basal levels and decreased E-ADA activity, possibly to increase the availability of adenosine, demonstrating a vascular protective effect and prevention of endothelial damage caused by excessive lipids in the blood. However, tucumã was not able to prevent the increase of lipid levels and biochemical changes caused by the induction of hyperlipidemia. By modulating the activities of purinergic enzymes, tucumã may contribute to the maintenance of vascular homeostasis, reducing platelet aggregation and subsequent atherothrombosis. Thus, tucumã may benefit patients with hyperlipidemia and is a promising alternative for reducing the number of cases of cardiovascular diseases.